Enhanced Torque Control and Reduced Switching Frequency in Direct Torque Control Utilizing Optimal Switching Strategy for Dual-Inverter Supplied Drive - M. Khairi Rahim; Auzani Jidin; Tole Sutikno (Institute of Advanced Engineering and Science, 2016)
Direct Torque Control (DTC) of induction machine has received wide acceptance in many adjustable speed drive applications due to its simplicity and high performance torque control. However, the DTC using a common two-level inverter poses two major problems such as higher switching frequency (or power loss) and larger torque ripple. These problems are due to inappropriate voltage vectors which are selected among a limited number of voltage vectors available in two-level inverter. The proposed research aims to formulate an optimal switching strategy using Dual-Inverter Supplied Drive for high performances of DTC. By using dual-inverter supplied, it provides greater number of voltage vectors which can offer more options to select the most appropriate voltage vectors. The most appropriate voltage vectors should able to produce minimum torque slope but sufficient to satisfy torque demands. The identification is accomplished by using an equation of rate of change of torque which is derived from the induction machine equations. The proposed strategy also introduces a block of modification of torque error status which is responsible to modify the status such that it can determine the most optimal voltage vectors from a look-up table, according to motor operating conditions. The improvements obtained are as follows; 1) minimization of switching frequency (reduce power loss), and 2) reduction of torque ripple. Some improvements obtained in the proposed strategy were verified via experimentations.